Body Area Networks - G. Prabhakara Reddy; P. Bhaskara Reddy; V. Koti Reddy (Journal of Telematics and Informatics, 2013)
Recent technological advances in integrated circuits, wireless networks, and physiological sensing have enabled miniature, lightweight, low power, intelligent monitoring devices to be integrated into a Body Area Network (BAN). This new type of technology hold much promise for future patient health monitoring. BANs promise inexpensive, unobtrusive, and unsupervised ambulatory monitoring during normal daily activities for long periods of time. However, in order for BANs to become ubiquitous and affordable, a number of challenging issues must be resolved, such as integration, standardisation, system design, customisation, security and privacy, and social issues. This paper presents an overview of many of these issues and indeed the background and rationale of body area networks.